2021
DOI: 10.1007/s00125-021-05562-9
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban compared with low-dose aspirin in individuals with type 2 diabetes and high cardiovascular risk: a randomised trial to assess effects on endothelial function, platelet activation and vascular biomarkers

Abstract: Aims/hypothesis Individuals with type 2 diabetes mellitus and subclinical inflammation have stimulated coagulation, activated platelets and endothelial dysfunction. Recent studies with the direct factor Xa inhibitor rivaroxaban in combination with low-dose aspirin demonstrated a significant reduction of major cardiovascular events, especially in individuals with type 2 diabetes and proven cardiovascular disease. Therefore, we asked the question of whether treatment with rivaroxaban could influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Some preclinical evidence showed the anti-inflammatory effects of rivaroxaban in inducing atherosclerotic plaque stabilization, 2 reducing serum levels of proinflammatory molecules such as monocyte chemoattractant protein-1 (MCP-1), IL-6, and tumor necrosis factor-alpha (TNF-α) 3 and inhibiting FXa-mediated macrophage inflammasome activities in ApoE −/− mice. 4 Moreover, some clinical studies confirmed the decreased serum levels of inflammatory markers among patients with atrial fibrillation (AF) 5,6 or diabetes 7 on rivaroxaban therapy at standard (20/15 mg OD) or nonapproved reduced dose (5 mg TD). No data are available about the anti-inflammatory effects of rivaroxaban 2.5 TD and aspirin 100 mg among patients with CAD and/or PAD.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some preclinical evidence showed the anti-inflammatory effects of rivaroxaban in inducing atherosclerotic plaque stabilization, 2 reducing serum levels of proinflammatory molecules such as monocyte chemoattractant protein-1 (MCP-1), IL-6, and tumor necrosis factor-alpha (TNF-α) 3 and inhibiting FXa-mediated macrophage inflammasome activities in ApoE −/− mice. 4 Moreover, some clinical studies confirmed the decreased serum levels of inflammatory markers among patients with atrial fibrillation (AF) 5,6 or diabetes 7 on rivaroxaban therapy at standard (20/15 mg OD) or nonapproved reduced dose (5 mg TD). No data are available about the anti-inflammatory effects of rivaroxaban 2.5 TD and aspirin 100 mg among patients with CAD and/or PAD.…”
Section: Discussionmentioning
confidence: 97%
“…1 The underlying mechanisms explaining these latter CV benefits are not clearly understood; however, previous evidence suggested an anti-inflammatory effect of rivaroxaban in different clinical settings. [2][3][4][5][6][7] Particularly, interleukin-6 (IL-6) is a proinflammatory cytokine which plays a key role in the pathogenesis of atherosclerosis 8 ; its serum levels were associated with atherosclerotic CV events and mortality. 9 Our explorative observational study aimed to evaluate the effects of the association of rivaroxaban and aspirin on plasma inflammation and coagulation markers among real-world patients with CAD and/or PAD.…”
Section: Introductionmentioning
confidence: 99%
“…We, therefore, chose a dose of 10 mg/kg/day, at which improvement in vascular remodeling provided data to support the benefits of low-dose aspirin. Although aspirin has been comprehensively used in populations, comparatively, its clinical reports about arterial stiffness are not too many [ 19 , 61 , 62 ], and none of them involve mechanism explanation. It is taken for granted anti-platelet effect duo to direct correlation of platelet activation with arterial stiffness [ 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, rivaroxaban prevented replicative senescence in HUVECs and aortic endothelial cells, restored endothelial function and prevented the progression of atherosclerosis [ 97 ]. A clinical study with type 2 diabetes mellitus and subclinical inflammation showed that rivaroxaban compared to Aspirin could improve endothelial function based different measures such as post-ischaemic forearm blood flow during reactive hyperaemia, skin blood flow, sP-Selectin or platelet-derived microparticles which stimulate endothelial repair [ 98 ].…”
Section: Methodsmentioning
confidence: 99%